Becoming a Communicative Partner: Infant Contingent Responsiveness to Maternal Language and Gestures. (12th October 2017) - Kuchirko, Yana; Tafuro, Lisa; Tamis LeMonda, Catherine S.
Abstract : Infant contingent responsiveness to maternal language and gestures was examined in 190 Mexican American, Dominican American, and African American infant–mother dyads when infants were 14 and 24 months. Dyads were video‐recorded during book‐sharing and play. Videos were coded for the timing of infants' vocalizations and gestures and mothers' referential language (i.e., statements that inform infants about objects and events in the world; e.g., "That's a big doggy!"), regulatory language (i.e., statements that regulate infants' attention or actions; e.g., "Look at that", "Put it down!"), and gestures. Infants of all three ethnicities responded within 3 sec of mothers' language and gestures, increased their responsiveness over development, and displayed specificity in their responses: They vocalized and gestured following mothers' referential language and gestures, but were less likely than chance to communicate following mothers' regulatory language. At an individual level, responsive infants had responsive mothers.